Theoretical Analysis on Stress and Deformation of Overburden Key Stratum in Solid Filling Coal Mining Based on the Multilayer Winkler Foundation Beam Model. (27th February 2021) - Ma, Chao; Guo, Xiaoqian; Zhang, Lianying; Lu, Aihong; Mao, Xianbiao; Li, Bing
Abstract : Solid backfill coal mining (SBCM) is a green mining technology which can effectively alleviate the environmental problems induced by traditional coal mining techniques, such as surface subsidence, water resources loss, coal gangue occupation, and pollution. In this study, a multilayer Winkler foundation beam model for the overburden key strata is proposed, and the model with two key strata is solved. The subsidence, rotating angle, inner force, and stress of the overburden key strata are systematically analyzed under various backfill elastic modulus, mining height, and soft layer thickness. The results show that the subsidence of the key strata exhibit "basin"-shape curves, and the backfill elastic modulus, mining height, and the thickness of the soft strata have significant influences on the subsidence of the key strata. The shear stress, horizontal stress, and vertical stress of key stratum can be effectively reduced by increasing the backfill elastic modulus. The increase of mining height has little influence on the stress of key stratum that close to the coal seam (key stratum #1), but has a significant effect on the stress of key stratum that above the soft layers (key stratum #2). On the contrary, the effect of increasing soft layer thickness on the stress of key stratum is opposite to that of increasing mining height. In addition, the shear failure of key stratum #1 at mining boundary and the tensile failures on both sides of mining boundary should be preferentially considered in SBCM engineering design. Due to the low shear stress level of key stratum #2, the tensile failure on both sides of the mining boundary should be mainly considered.